2011
DOI: 10.1002/mnfr.201100080
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates diabetic nephropathy by inhibiting PKC‐α and PKC‐β1 activity in streptozotocin‐induced type I diabetic rats

Abstract: These results prove that curcumin produces dual blockade of both PKC-α and PKC-β1 activities, which suggests that curcumin is a potential adjuvant therapy for the prevention and treatment of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 55 publications
0
78
0
Order By: Relevance
“…35 Meanwhile, mice harboring two point mutations in the Mll2 gene, which encodes one of the H3K4 methyltransferases, exhibit spontaneous insulin resistance. 36 Of interest, Soetikno et al 37 have shown that curcumin, a nonspecific p300 inhibitor, alleviates diabetic nephropathy in STZ-injected rats. Our data allude to a scenario where high glucose engages p300 and WDR5 in collagen activation and tubulointerstitial fibrosis and reinforce the notion that screening for small molecule compounds that can inhibit the activities of these proteins may yield novel therapeutic solutions.…”
Section: Discussionmentioning
confidence: 99%
“…35 Meanwhile, mice harboring two point mutations in the Mll2 gene, which encodes one of the H3K4 methyltransferases, exhibit spontaneous insulin resistance. 36 Of interest, Soetikno et al 37 have shown that curcumin, a nonspecific p300 inhibitor, alleviates diabetic nephropathy in STZ-injected rats. Our data allude to a scenario where high glucose engages p300 and WDR5 in collagen activation and tubulointerstitial fibrosis and reinforce the notion that screening for small molecule compounds that can inhibit the activities of these proteins may yield novel therapeutic solutions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the definite proximate regulators linking ET-1 and VEGF signaling in diabetic hearts have not yet been identified. TGF-b and CTGF are involved in extracellular matrix (ECM) accumulation both in the early and the later stages of diabetes (26). Several lines of experimental and clinical evidence support a major role for TGF-b in develop- (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Four days after the STZ injection, blood sugar was assessed in overnight-fasted rats using a glucometer (SD Biosensor India, New Delhi, India) and 80 % of rats were found to have developed diabetes; rats with blood glucose levels >17 mmol/L were considered diabetic. 35 These rats were maintained in the diabetic condition for 40 days, with a 90 % survival rate, to achieve DN. Each rat was placed in a metabolic cage to collect urine for biochemical analysis and rats with proteinuria were randomly divided into a DN control group (Group 2) and a PTY-2-treated group (Group 3; n = 6 rats in each group).…”
Section: Experimental Protocol and Induction Of Dnmentioning
confidence: 99%